1994
DOI: 10.1038/bjc.1994.165
|View full text |Cite
|
Sign up to set email alerts
|

Formation and loss of O6-methyldeoxyguanosine in human leucocyte DNA following sequential DTIC and fotemustine chemotherapy

Abstract: There is increasing evidence to indicate that O6-methyldeoxyguanosine (O6-MedG) formation in DNA is a critical cytotoxic event following exposure to certain anti-tumour alkylating agents and that the DNA repair protein O6-alkylguanine-DNA alkyltransferase (ATase) can confer resistance to these agents. We recently demonstrated a wide inter-individual variation in the depletion and subsequent regeneration of ATase in human peripheral blood lymphocytes following sequential DTIC (400 mg m-2) and fotemustine (100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…The very clear differences indicate that the close correlation between the levels of DNA alkylation in normal and tumor tissue despite the very large difference in the levels of DNA damage might be partially correlated to the individual differences in modes of alkylating agent metabolism due to genetic polymorphism and/or DNA repair pathways. 55,57 Previous studies with urinary bladder 54 and other tissues 58,59 have indicated that higher levels of the DNA repair protein (i.e., O 6 -alkylguanine DNA alkyltransferase) may result in lower levels of O 6 -methylguanine in DNA. Therefore, the change towards a malignant phenotype could possibly be attributed in part to the differences in DNA repair levels.…”
Section: Discussionmentioning
confidence: 99%
“…The very clear differences indicate that the close correlation between the levels of DNA alkylation in normal and tumor tissue despite the very large difference in the levels of DNA damage might be partially correlated to the individual differences in modes of alkylating agent metabolism due to genetic polymorphism and/or DNA repair pathways. 55,57 Previous studies with urinary bladder 54 and other tissues 58,59 have indicated that higher levels of the DNA repair protein (i.e., O 6 -alkylguanine DNA alkyltransferase) may result in lower levels of O 6 -methylguanine in DNA. Therefore, the change towards a malignant phenotype could possibly be attributed in part to the differences in DNA repair levels.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was isolated from rat pyloric tissues as previously described (25) using phenol and chloroform but with the proteinase K digestion carried out at 4°C. DNA purity was assessed by UV absorbance at 260 and 280 nm using a Shimadzu UV-160 spectrophotometer, and samples were considered to be pure if the 260 nm/280 nm ratio was between 1.7 and 1.9.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas all wbc DNA samples contained (apparently) detectable levels of 80HG, in 2 studies it was reported that a limited number of individuals had no detectable bulky adducts (37,52) (11,65). Similarly, levels of bulky DNA adducts in smokers ranged from 1.9 to 25.3 (lung) and from <0.1 to 21.9 (liver) adducts/101 dN (11,65 (40), and in liver DNA, 80HG levels were several orders of magnitude higher than bulky DNA adducts and other adducts arising from endogenous processes such as lipid peroxidation (8,48 (58) and sperm DNA (20) and also bulky DNA adducts in stomach tissue (18 (41).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Figure 5 shows the variation in the formation and persistence of 06-MeG in wbc DNA following treatment of 3 individuals with the same doses of the methylating agent dacarbazine (DTIC) and fotemustine (41 (19,49).…”
Section: Introductionmentioning
confidence: 99%